Effects of adding biochar on the properties and nitrogen bioavailability of an acidic soil. (July 2017) - Wang, Z. Y.; Chen, L.; Sun, F. L.; Luo, X. X.; Wang, H. F.; Liu, G. C.; Xu, Z. H.; Jiang, Z. X.; Pan, B.; Zheng, H.
Abstract : Biochar has attracted global attention because of its widespread application to improve soil quality and enhance soil productivity. Five types of biochar were prepared from peanut shells at 200–600°C by slow pyrolysis, and their physicochemical properties were investigated. Biochar was produced at 300 and 400°C, PBC300 and PBC400, respectively. The two forms of biochar were evaluated as soil amendments with an incubation and a pot experiment in a soil that had become acidified because of excessive use of nitrogen (N) fertilizers. The PBC300 and PBC400 additions significantly decreased the soil bulk density and increased the pH, cation exchange capacity (CEC) and soil organic matter (SOM) content. Both types of biochar significantly decreased NH4 + ‐N and NO3 − ‐N contents as a result of N immobilization, reduced nitrification because of the enhanced microbial activity (determined by the fluorescein diacetate method) and reduced the abundance of ammonia‐oxidizing bacteria (AOB). The growth of maize ( Zea mays L . ) was stimulated and, compared with the unamended soil, the biomass increased by 15.2–32.7% following the addition of PBC300 or PBC400. Maize root morphology (e.g. length and tips) and the properties of the rhizosphere soil (e.g. CEC and pH) were improved by the addition of biochar, leading to enhance N bioavailability by decreasing NAE (N accumulation efficiency) and increasing NUE (N utilization efficiency). In general, the ameliorating effects of PBC400 on the acidic soil were superior to those of PBC300. These results indicate that producing a specific type of biochar based on pyrolytic temperature might be an alternative strategy for selecting the most appropriate biochar for a specific soil. Highlights: Biochar was selected for an acidic soil based on the pyrolytic temperature. Biochar decreased the soil bulk density and increased the soil pH, CEC and SOM. Biochar slowed nitrification by decreasing the abundance of ammonia‐oxidizing bacteria (AOB). Adding biochar stimulated maize growth and improved N bioavailability.